Thermal Modelling for Permanent Magnet Synchronous Machine (PMSM) - R. Aziz; G. J. Atkinson; S. Salimin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
It is important to predict the temperature in some of the essential parts in machine design to prevent the machine from any damage. Most researchers usually not given much attention on thermal analysis during machine design as much as the electromagnet design. Therefore, in this study, two types of thermal modelling were proposed to predict the temperature of a permanent magnet synchronous machine (PMSM). Infolytica ThermNet software has been used since the software is related to Infolytica Magnet and the losses obtained from the electromagnetic field analysis are used as the heat source in the thermal analysis. Comparison has been done between the predicted temperature from lumped parameter model and finite element analysis. The results also will be validated by using experimental setup. Since Infolytica Magnet has been used to analyse the electromagnetic output therefore finite element analysis model is the better choice.